Effect of Urea Super Granule on Growth and Yield of Wheat - Islam, MS; Biswas, GC; Karmoker, MC; Suem, MA (Journal of Environmental Science and Natural Resources, 2012)
A field experiment was carried out at Agronomy Field, Bangladesh Agricultural University (BAU), Mymensingh during the period from November 2009 to March 2010 with a view to finding out the effect of appropriate dose of USG on growth and yield of wheat. Six levels of nitrogen (T0, T1, T2, T3, T4 and T5) were applied as treatments for growth and yield of wheat var. Bijoy for this study. Among the application of USG, treatment T5 produced the superior results on morpho-physiological and growth characters of wheat except number of non sterile spikelet where USG treatment T2 performs the best (1.82). As results, T5 produced the highest plant height (95.77 cm), number of total tiller hill-1 (4.96), no. of effective tiller (4.13), no of non effective tiller (1.00), number of total spikelet (20.22), no of spikelet spile-1 (10.92), sterile spieklet (18.70), no of grains spike-1 (46.27), 1000-grain yield (51.39 g), grain yield (2.42 t ha-1) and straw yield (4.06 tha-1). DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10164 J. Environ. Sci. & Natural Resources, 4(2): 143-146, 2011